Scientific research project: Biomechanical analyses at the 12th IAAF World Championships in athletics 2009. Final report. Sprint & hurdles women. - Graubner, R.; Buckwitz, R.; Landmann, M.; Starke, A. (DLV, 2009)
Final report of the biomechanical analyses of the women's sprint and hurdle events at the 12th IAAF World Championships in athletics, Berlin 12.-23. August 2009 within the frame of a project of the German Athletics Federation (DLV) in co-operation with the Institute of Applied Training Science Leipzig, The Olympic Training Bases Berlin, Hesse and Rhineland and the Martin-Luther-University Halle/Wittenberg.